PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP KEPUTUSAN PENGGUNAAN JASA (STUDI KASUS PELANGGAN PT. SILKARGO CABANG SEMARANG DOMISILI JEPARA DAN SEMARANG) - Driantama Aryo H; Agung Budiatmo (Jurnal Ilmu Administrasi Bisnis, 2019)
Competition in the world of freight forwarding services has increased considerably in recent years. PT. SILkargo Semarang Branch in 2011-2017 experienced a fluctuating trend. 2014-2017 always experiences a decrease in usage and the realization of customer acquisition has never been on target. There are complaints from customers about the quality of service of PT. SILkargo. The type of research used is explanatory research and in this study the entire population is sampled or called a census, collecting data using a questionnaire. The number of samples used was 100 respondents divided into two cities with the highest customer acquisition, namely for the 70 respondents in the Jepara region and 30 respondents from the Semarang area. This study uses quantitative and qualitative analysis with validity, reliability, correlation coefficients, coefficient of determination, simple and multiple regression, significance of t test, and F test with the help of SPSS version 24 program. The results of the study show that the quality of service variables and brand ideals have a strong and positive influence on service use decisions. Service quality and brand image variables show 0.656 that the relationship between the two variables to service use decisions has a strong relationship. The service quality variable in the determination test (R square) shows 33.3% influence purchasing decisions, so 66.7% is influenced by other factors. The brand image variable in the determination test (R square) shows that 30.2% affects purchasing decisions, so 69.8% is influenced by other factors. PT. SILkargo must be more active in contacting customers and providing training so that employees are more skilled in managing documents, then the freight network must be more extensive the company must have a network to remote points in Indonesia and networks to countries that have high potential for shipping goods.